Correction: Assessment of pozzolanic activity of thermally activated clay and its impact on strength development in cement mortar. Issue 14 (19th February 2015) - Amin, Noor-ul-; Alam, Sultan; Gul, Saeed
<x xml:space="preserve">Abstract</x> Correction for 'Assessment of pozzolanic activity of thermally activated clay and its impact on strength development in cement mortar' by Noor-ul- Amin et al., RSC Adv., 2015, 5, 6079–6084.